KOMPETENSI GURU DALAM PENYUSUNAN INSTRUMEN PENILAIAN MATA PELAJARAN PENDIDIKAN AGAMA ISLAM - Uljanah, Nida; Amaliyah, Putri Ayu; Dalili, Cut Intan; Apriyanto, Dwi; Fathurrohman, F (Institut Islam Mamba'ul 'Ulum Surakarta, 2024)
Teacher competence is a very important aspect to improve the quality of education. The competencies that must be owned by a teacher consist of pedagogic, personality, professional and social competencies. Whereas PAI learning is a process of forming knowledge, attitudes and skills through fact-based cognitive performance and contextual socio-religious phenomena. The formulation of the problems in this study are: 1) What are the scopes of PAI learning?, 2) What competencies must a teacher have?, and 3) What are the principles and techniques in preparing PAI assessment instruments?. The purpose of this study was to determine the scope of Islamic religious education learning, describe the competencies that must be possessed by a teacher, and find out what principles and techniques are used in compiling Islamic religious education assessment instruments. This research is expected to provide benefits for all education stakeholders to be used as a reference in improving teacher competence. The method used in this research is library research with a qualitative approach.